Causes of unwanted pregnancy among adolescents in Bali Province: a qualitative study - Kadek Anggie Wisandewi Mayun; Luh Seri Ani; Ni Luh Putu Suariyani (Universitas Udayana, 2017)
Background and purpose: Teenage pregnancy is a major contributing factor of high maternal and infant mortality rates in Indonesia. Unwanted pregnancy among adolescents is increasing, therefore an understanding of its causes is essential. This study aims to explore causes of unwanted pregnancy among adolescents. Methods: A qualitative study was conducted in Bali Province. Data were obtained through in-depth interviews with 10 adolescents aged between 12-21 years who experienced unwanted pregnancy. Data were collected between September and October 2016. Data were analysed thematically and presented using a narrative approach. Results: Our study revealed that determinants associated to unwanted pregnancy among adolescents included the lack of systematic education on sexual and reproductive health both at home and school, as well as the lack of self-efficacy of teenage girls to reject pre-marital sex with their partner. Our study found that this pre-marital sex was done as an expression of love, because of being forced by the partner, and due to stressful home environments. Conclusions: The main causes of unwanted pregnancy among adolescents are the lack of sexual and reproductive health education and a weak self-efficacy of teenage girls to reject pre-marital sex demanded by their partner. Given the complexities of teenage pregnancy, overarching policy to facilitate an early comprehensive sexual and reproductive health education program at home, schools, and youth-friendly health facilities is warranted.